PENGOLAHAN DAN PENYAJIAN KUDAPAN MAKANAN SEHAT BERGIZI MOCHI UBI UNGU DI GKAI GADING SERPONG - Wahyu Irawati; Pingkan Imelda Wuisan; Imanuel Adhitya Wulanata Chrismastianto; Ashiong Parhehean Munthe; Clement Khrisman Laia; Damai Yanti Manalu (Lembaga Penelitian dan Pengabdian kepada Masyarakat (LPPM), Univesitas Kristen Indonesia, 2024)
Community Service (PkM) is a means of carrying out the mission of Universitas Pelita Harapan which is to contribute to the advancement of science and culture based on Biblical Christian insights and participate in the development of individuals and society for the glory of God. PkM activities were carried out at the Indonesian Bible Christian Church on Jalan Raya Kelapa Dua, Ruko Blitz, Blok A No. 28, Gading Serpong, Tangerang, Banten. The needs analysis based on the questionnaire showed that the congregation did not fully understand how to have healthy snacks at an affordable price. The low economic condition of the congregation makes the congregation prefer to consume cheap and unhealthy food without paying attention to the health of the body. The objectives of the PkM were to 1) provide counseling on nutritious snacks, and 2) conduct training on making purple sweet potato mochi. PkM was held on September 2, 2023, attended by 20 people, delivered by lecture demonstration method. The results of PkM based on the results of the evaluation questionnaire can be seen that 77% of respondents stated that the material presented was very clear, 55.6% agreed that watching YouTube mochi making that had been given helped to practice it at home, 55.6% strongly agreed that they were interested in practicing it at home, and 44.4% of respondents strongly agreed that making purple sweet potato mochi was easy to do. Keywords: Nutritious; snack; mochi; healthy; purple sweet potato